From fracture to function: a Baird and Jackson score-based evaluation of bimalleolar ankle injuries - Yadav, Saurabh; Asif, Adnan; Modi, Nihar; Sheikh, Shanshah; Panchal, Lalit (International Journal of Research in Orthopaedics, 2025)
Background: Bimalleolar ankle fractures are common injuries that significantly impact mobility and quality of life. Open Reduction and Internal Fixation (ORIF) remains the standard for displaced fractures, though limited evidence exists regarding outcomes of combined fibular plating with screw or tension band fixation for the medial malleolus in Indian populations. Methods: This prospective observational study was conducted at a secondary care teaching hospital in India. Thirty patients aged 18–65 years with displaced closed bimalleolar fractures underwent ORIF. The lateral malleolus was fixed with a one-third semi tubular or anatomical plate, while the medial malleolus was fixed with either cannulated cancellous (CC) screws (n=18) or tension band wiring (TBW) (n=12). Patients were followed up for three months and functional outcomes were assessed using the Baird and Jackson scoring system. Results: The mean age was 37.9 years; males comprised 63.3% of cases. Road traffic accidents were the predominant cause (60%), with Supination-External Rotation being the most frequent injury mechanism. Weber type B fractures were most common (53.3%). At three months, functional outcomes were excellent in 43.3%, good in 36.7%, fair in 16.7% and poor in 3.3% of patients. The mean Baird and Jackson score was 93.4±4.57. Postoperative complications occurred in 26.7% (stiffness in 4, superficial infection in 4), all managed conservatively. Conclusions: ORIF with fibular plating and medial malleolus fixation using CC screws or TBW provides favourable short-term functional outcomes and minimal complications. Larger studies with longer follow-up are needed to further validate these findings.